2019
DOI: 10.3390/app9235200
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic State Estimation for Synchronous Machines Based on Adaptive Ensemble Square Root Kalman Filter

Abstract: Dynamic state estimation (DSE) for generators plays an important role in power system monitoring and control. Phasor measurement unit (PMU) has been widely utilized in DSE since it can acquire real-time synchronous data with high sampling frequency. However, random noise is unavoidable in PMU data, which cannot be directly used as the reference data for power grid dispatching and control. Therefore, the data measured by PMU need to be processed. In this paper, an adaptive ensemble square root Kalman filter (AE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Meanwhile, the UKF and CKF exhibit almost the same performance. Recently, the Kalman filter has been developed in practical systems, such as the distributed Kalman filter [ 37 ] for sensor networks, hybrid Kalman filter [ 38 ], and adaptive ensemble square root Kalman filter [ 39 ].…”
Section: State Estimation Based On a Distinct Modelmentioning
confidence: 99%
“…Meanwhile, the UKF and CKF exhibit almost the same performance. Recently, the Kalman filter has been developed in practical systems, such as the distributed Kalman filter [ 37 ] for sensor networks, hybrid Kalman filter [ 38 ], and adaptive ensemble square root Kalman filter [ 39 ].…”
Section: State Estimation Based On a Distinct Modelmentioning
confidence: 99%
“…In [2], an adaptive ensemble square root Kalman filter (AEnSRF) has been proposed, in which the ensemble square root filter (EnSRF) and Sage-Husa algorithm are utilized to estimate measurement noise online. Simulation results obtained by applying the proposed method showed that the estimation accuracy of AEnSRF is better than that of ensemble Kalman filter (EnKF), and AEnSRF can track the measurement noise when the measurement noise changes.…”
Section: Published Papersmentioning
confidence: 99%
“…Since the CKF often encounters the problem of filter divergence and the loss of positive definiteness caused by the computational errors of arithmetic operations in practical applications [16], the SCKF, originally proposed by Ienkaram and Haykin, propagates the square root of the error covariance matrix to improve stability and accuracy [2], [18], [30]. As a result, the SCKF, as an improvement to the CKF, has shown promise in nonlinear systems and has been used for state estimation with unknown noise.…”
Section: The Square-root Cubature Kalman Filtermentioning
confidence: 99%